Extratos vegetais no controle de podridão parda (Monilinia fructicola) em pêssego - Flores, Mariana Faber (2013)
The brown rot [Monilinia fructicola (Winter) Honey] is the most important disease in peach, causing damage to flowers and fruits in pre and post-harvest. The use of pesticides in agriculture has caused risks to human health and the environment. In the search for alternative methods for control brown rot in postharvest, experiments were performed in order to evaluate the efficiency of different plant extracts to control M. fructicola. Two experiments were conducted in vitro and four experiments in vivo. In the experiment 1, in vitro, was assessed the germination of conidia in Elisa plate containing five treatments: aqueous extract of canola, alcoholic, maceration, infusion and control with five repetitions. For mycelial growth were evaluated different concentrations (0, 2.5, 5.0, 7.5 and 10%) of the aqueous extract of canola with seven repetitions. The four in vivo experiments were performed in a completely randomized design consisting of four replications, represented by plastic trays containing five fruits each. Mechanical damage were made in equatorial portion of each fruit and then applied treatments (extracts) by dipping. Thereafter, the fruits were inoculated with a spore suspension of 105 mL-1 of M. fructicola, and after four days, was evaluated the lesion area (cm2) and the number of spores. In experiments 2 and 3, in vivo, we assessed the plant extracts of canola (Brassica napus), guaçatonga (Casearia sylvestris), eucalyptus (Eucalyptus citriodora) and babosa (Aloe vera) compared to the chemical treatment and the control. The experiment 4 consisted in factorial 3x3 + 1 control, and the factor A consists by the species of brassicas (canola, cabbage and turnip) and factor B the forms of extraction (alcoholic infusion and maceration). The experiment 5 consisted in a 3x2 factorial design, with the factor A consisting of the types of injuries (hole, scraping and without injuries) and factor B using the extract (with and without extract canola). The aqueous extracts of canola, maceration and infusion inhibited conidial germination and mycelial growth. The extract of canola in concentration of 10% showed the best results, both, in the first assessment, as in the second, with 78 and 69% of control, respectively. In the in vivo experiments, all treatments were subjected to the control of canola extract showed significantly less damage when compared to their respective controls. The different forms of extraction tested were effective in controlling the pathogen, and for each species there was a way to extract that stood out, and canola for the best extraction was by infusion, for the turnip was maceration and the cabbage was by alcohol extraction. The species of brassicas reduced production and spore germination of M. Fructicola in post-harvest peaches. The treatments undergone perforation (hole) presented itself as an effective methodology to evaluate the efficiency of the extract of canola.